Mostni žerjavi v intralogistiki - Lerher, Tone (University of Maribor Press, 2022)
Industrial Overhead Cranes in Intralogistics. The textbook deals with transport devices for lifting loads in logistics. In addition to a brief historical overview of the use of transport and lifting techniques, individual variants of lifts and cranes used in practise are presented. The textbook deals specifically with industrial overhead cranes in intralogistics and their basic components. The European standard EN 13001 is cited, which is a recognised and established standard for the design of industrial overhead cranes in Slovenia and beyond. Standardised analytical and empirical expressions are given to determine the selection of lifting rope diameter according to EN 13001-2: 2014 and the selection of load hook according to EN 13001-3-5: 2016.